Obstruksi Saluran Nafas Atas grade III ec Kassabach Merrit Syndrome + Bronchopneumonia+DIC - Intanri Kurniati; Risti Graharti; Agustyas Tjiptaningrum; Evi Kurniawati (CV. Jasa Sukses Abadi, 2022)
Upper airway obstruction is a blockage in the larynx caused by inflammation, foreign bodies, trauma, tumors so that ventilation is disrupted. One of the causes is hemangioma, which is the most common soft tissue tumor in newborns. In the state of hemangiomas, sometimes also found a syndrome in the form of Kasabach-Merritt Syndrome. As many as 20% of patients with KMS exhibit unusual symptoms compared to cutaneous hemangiomas. Clinical symptoms that can occur in upper respiratory tract obstruction include hoarseness, dysphony to aphony, shortness of breath (dyspnea), stridor (breath sounds) inspiration, suprasternal, epigastric, supraclavicular and intercostal retractions on inspiration. Kasabach-Merritt Syndrome is rare because the diagnosis is often delayed. KMS is more common in boys than girls. Ultrasound examination, Computer Tomography (CT) Scan, Magnetic Resonance Imaging (MRI) can help to determine the nature and extent of the lesion and identify the involvement of organs in the body. Extensive bleeding in KMS can cause consumptive coagulopathy that occurs due to excessive use of coagulation factors such as fibrinogen. Coagulopathy will progress to Disseminated Intravascular Coagulation (DIC) and even death. From this condition, the patient also experienced bronkopneumonia which is an acute infection of the lungs affecting the lung lobules starting from the lung parenchyma which can be caused by various etiologies such as bacteria, viruses, fungi and foreign bodies. This is because patients have a susceptibility to infection due to their condition.